Effect of the Phosphodiesterase 5 Inhibitor Sildenafil on Ischemia-Reperfusion-Induced Muscle Mitochondrial Dysfunction and Oxidative Stress - Liliane Tetsi; Anne-Laure Charles; Isabelle Georg; Fabienne Goupilleau; Anne Lejay; Samy Talha; Myriam Maumy-Bertrand; Claire Lugnier; Bernard Geny (MDPI AG, 2019)
Lower-limb ischemia-reperfusion (IR) is frequent and associated with significant morbidity and mortality. Phosphodiesterase 5 inhibitors demonstrated antioxidant and beneficial effects in several organs submitted to IR, but their effects on muscle mitochondrial functions after lower-limb IR are unknown. Unilateral hindlimb IR (2 h tourniquet followed by 2 h reperfusion) without or with sildenafil (1mg/kg ip 30 minutes before ischemia) was performed in 18 mice. Maximal oxidative capacity (VMax), relative contribution of the mitochondrial respiratory chain complexes, calcium retention capacity (CRC)—a marker of apoptosis—and reactive oxygen species (ROS) production were determined using high-resolution respirometry, spectrofluorometry, and electron paramagnetic resonance in gastrocnemius muscles from both hindlimbs. IR significantly reduced mitochondrial VMax (from 11.79 ± 1.74 to 4.65 ± 1.11 pmol/s*mg wet weight (ww), p < 0.05, −50.2 ± 16.3%) and CRC (from 2.33 ± 0.41 to 0.84 ± 0.18 µmol/mg dry weight (dw), p < 0.05; −61.1 ± 6.8%). ROS tended to increase in the ischemic limb (+64.3 ± 31.9%, p = 0.08). Although tending to reduce IR-related ROS production (−42.4%), sildenafil failed to reduce muscle mitochondrial dysfunctions (−63.3 ± 9.2%, p < 0.001 and −55.2 ± 7.6% p < 0.01 for VMax, and CRC, respectively). In conclusion, lower limb IR impaired skeletal muscle mitochondrial function, but, despite tending to reduce ROS production, pharmacological preconditioning with sildenafil did not show protective effects.